AC$^3$ - Automatic Cartography of Cultural Contents - Ganascia, Jean-Gabriel (VIEW'06: Proceedings of the Visual Information Expert Workshop, 2006)
Experiences with e-books show that the principle obstacle to electronic reading is neither the weight, nor the autonomy or the discomfort of reading on screen, but the absence of reference mark which makes it possible to replace the current window of reading in the whole of the book. We present an automatic cartography of electronic documents which constitutes an attempt to facilitate navigation, reading and memorization of contents. It is to automatically build a singular picture which is designed to be associated to our remembering of each document, i.e. to our mental image. This picture corresponds to the cartography of an island. Its shape is build from the document structure; its coloring reflects the affective content of the text extracted by keywords spotting techniques while icons associated to document topics are added to textual legends as in ancient geographical maps.